(3GdQSGdI GdceGdjI aj GdMbGFb GdEdgjIs - (3GdJjej, GdHcQj, GdWHQSJGfj, GdQGRj, GdTGaYj, CHh YHO Gddg, GHf NWjH GdQj, aNQ GdOjf, eMeO Hf YeQ Hf GdMSf Hf GdMSjf, (B606 (3g`s ((3YHO GdcQjes)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B... (3cd eWdhH cGf hCHbi jchf HGdWdH (B... (3GdChd Cf eYdheg hehVhYg CTQa GdeYdheGJ(B...s
(3BNQgG (B:s
(3hdG jchf GdaUhd KeGfjI cPG hdG jchf Pdc GdaUhd eJSGhjI aj GdeOI Hd jchf eNJdaI hdeG hUd GdcdGe Edi gPG GdebGe(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B5(3, U(B137s
(3GdPQjYI, Qbe(B: 1104s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds